Collaboration and multimedia: identifying equilibrium in the MDT information ecosystem - LUZ, SATURNINO; KANE, BRIDGET (ACM, 2012)
his study of collaboration among a multidisciplinary team of healthcare workers demonstrates that elements intrinsic to the interaction constitute a delicate ecosystem. As the balance between actors, digital media and paper artefacts fluctuates, so too the nature of the interaction and collaboration changes. Intrinsic to the multidisciplinary team (MDT) ecosystem is specialist knowledge, radiological images, pathology samples, together with the interpretation of the patient's findings, as well as the roles and responsibilities of the active participants and observer collaborators.
ACM 2012 conference on Computer Supported Cooperative Work Companion
PUBLISHED
Seattle
Keywords: Teamwork; MDTMs; Medical Team Meetings; Collaboration; Cancer; Smart & Sustainable Planet